PENENTUAN TINGKAT KANDUNGAN AMONIAK, NITRIT, DAN NITRAT PADA REMBESAN SAMPAH LOKASI PEMBUANGAN AKHIR (LPA) AIR DINGIN KOTA PADANG - - Zilfa; - Zulfarman; - Hariyanti (Universitas Andalas, 2012)
Determination of amoniac, nitrite, and nitrate content in seepage waste water in landfill area in cold water, Padang have been done using spectrophotometric method. Sample took from sequencing ofseepage waste water treatment process. The results showed that the ammonia, nitrite, and nitrate content in seepage waste water were 137.612 to 400.298 mg/ L, 0.34 to 0.756 mg/ L, and 0.682 to5.842 mg/ L, respectively. The differences of ammonia, nitrite, and nitrate content in seepage waste water and ammonia and nitrite contents tend to decrease while the nitrate content tends to increase. The rate of ammonia degradation in water seepage was different for each sampling place where the rate of degradation was greatest in seepage water waste treatment II. This degradation is expected to reduce the level of pollution on the environment.